Antiracism Education Activism: A Theoretical Framework for Understanding and Promoting Racial Equity - Sarah Diem; Anjalé D. Welton; Jeffrey S. Brooks (AERA Open, 2022)
Although antiracism activism has contributed to substantive progress under certain circumstances and in certain contexts, little research attempts to theorize how antiracism activism is manifest across contexts. In this article, we explore individual and collective antiracist actions within and outside schools. We introduce a theoretical framework that identifies four domains of activism—policy, community, leadership, and teaching and learning—in which activists operate to make a positive difference in promoting racial equity and antiracism in education. The framework offers a systemic way of thinking about antiracist activism in education and the importance of recognizing that several aspects of antiracist activism usually conceived as distinct are interrelated within and across domains. Indeed, antiracist education activism must be understood holistically and systemically if we seek to dismantle the racism that is woven into every piece of the education system.